Estudo experimental e numérico de uma turbina eólica de eixo horizontal em escala reduzida com e sem difusor - SILVA, Artur José Cunha da (2022)
The global demand for renewable energy sources has increased significantly in recent years, among the best known forms is the wind energy that, driven by the collaboration of technology companies along with governments that are each Increasingly interested in this form of energy, has developed considerably in the last few decades. The horizontal axis wind turbines stand out among the other types in the wind generation, presenting the advantage of increasing their power generation capacity through the use of diffusers, which involve the turbine and accelerate the flow of air through the Rotor. In this context, laboratory studies in scale turbine models are of fundamental importance for the development of new technologies, from experimental methodologies complemented by the dynamics of computational fluids (CFD) is possible Predict the behavior of real-scale wind turbines within various operating conditions. The research of this work was developed on a horizontal didactic axis wind turbine with four-blade rotor and ABS material diffuser printed on a 3d printer. Experimental studies were developed in wind tunnel with the model on scale with and without diffuser, in addition to numerical simulations of the model via the CFX plugin of the commercial software Ansys Workbench. For the wind tunnel tests a closed PID mesh control system was developed integrated with an Arduino, responsible for the turbine rotation control through the PWM modulation of the brake applied on the equipment. Experimental data were obtained for wind speeds of 6, 7 and 8 meters per second, in each test the flow velocity was kept constant while the turbine rotation was gradually reduced by the modulation system, in order to plot the curve of Power (Cp) for different specific speeds of shovel tip (λ). The experimental results showed a considerable increase in the power extracted from the wind by the model in wind tunnel, arriving at 33% with the use of the diffuser at a wind speed of 8 meters per second.